PENEGAKAN HUKUM TERHADAP PELAKU PENIPUAN ARISAN ONLINE YANG MELAKUKAN LELANG ARISAN FIKTIF (Studi Kasus Perkara Polres Sukoharjo) - Rahmawati, Nadila Dwi (IDFoS Indonesia, 2022)
This research is a qualitative research. Data collection was conducted through interviews. This research aims to find out how law enforcement against the perpetrators of online arisan fraud by conducting fictitious arisan auctions. Based on the results of the latest research by Kaspersky Lab and B2B International in twenty-six countries, as many as 26% (twenty-six per cent) of Indonesian consumers have been victims of online fraud, the results of the study also show that 48 per cent of consumers have been the target of fraudulent actions. In overcoming online fraud, supporting components are needed, one of these components is the law enforcement officers themselves as human resources. Based on the results of the interview, it is concluded that law enforcement efforts carried out by the police are pursued through two stages, namely the prevention stage (preventive) and the enforcement stage (repressive). Prevention efforts (preventive) carried out by Sukoharjo police are by appealing to the public through social media and carrying out socialisation to the public. Repressive efforts are carried out through several stages, namely the investigation stage, investigation stage, examination stage, settlement stage and case submission to the public prosecutor (JPU).